Is running performance enhanced with creatine serum ingestion? - Astorino, T. A.; Marrocco, A. C.; Gross, S. M.; Johnson, D. L.; Brazil, C. M.; Icenhower, M. E.; Kneessi, R. J. (The Journal of Strength and Conditioning Research, 2005)
Runners Advantage (RA) creatine (Cr) serum has been marketed to increase running performance. To test this claim, cross-country runners completed baseline testing (BASE), an outdoor 5,000-m run followed by treadmill VO2max testing on the same day. Subjects repeated testing after ingesting 5 ml of RA (n = 13) containing 2.5 g of Cr or placebo (n = 11). Heart rate (HR), rating of perceived exertion (RPE), and run time were recorded. With RA (56.48 ± 8.93 ml/kg min), VO2max was higher (p = 0.01) vs. BASE (54.07 ± 9.36 ml/kg min), yet the magnitude of the increase was within the coefficient of variation of VO2max. No effect of RA on maximal HR was exhibited, yet VCO2max and duration of incremental exercise were significantly higher (p < 0.025) vs. BASE. VO2max was similar in PL (58.85 ± 6.67 ml/kg·min) and BASE (57.28 ± 7.22 ml/kg·min). With RA, the 5,000-m time was unchanged, and RPE was lower (p < 0.025) vs. BASE. These data do not support the ergogenic claims of RA in its current form and dose.